KERUKUNAN UMAT MELALUI INSTRUMENT EKONOMI SYARIAH DALAM PEMBENTUKAN TRANSFORMASI MASYARAKAT - Syahpawi Syahpawi (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2010)
This article talks about reconciliation of people /through economic instrument of syari'ah in forming of society transformasi. Failure of conventional system make happened deviation of value of social value and of normative society moral so that that system is assumed to fail in to form reconciliation of people in economic tatanan. For that economic intstrument of syari'ah represent one of the alternatives in forming of society transformation with mudharabah instrument, maal baitul, religious obligatory institute, communal ownership institute, alms and all that.